On Reason : Rationality in a World of Cultural Conflict and Racism - Eze, Emmanuel Chukwudi (Book collections on Project MUSE., 2008)
A philosophical argument that rationality is based on, or produced from, difference, and is not only worth retaining but necessary in a culturally diverse world.